2021
DOI: 10.3389/fenvs.2021.638891
|View full text |Cite
|
Sign up to set email alerts
|

The Coupling Coordinated Relationship Between New-type Urbanization, Eco-Environment and its Driving Mechanism: A Case of Guanzhong, China

Abstract: As an important platform for participating in international competition and cooperation, supporting economic growth and promoting coordinated regional development, urban agglomeration plays an important role in China’s economic, social and urbanization development. At this time, the Guanzhong Plain urban agglomeration (GZPUA), as the second largest urban agglomeration in western China, has a moderate population density. The high demand and high input of resources for population growth make the regional ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 74 publications
(39 reference statements)
0
27
0
Order By: Relevance
“…Yang analyzed the spatio-temporal variations of ecological footprints and ESV from 2005 to 2017 in the Guanzhong Plain Urban Agglomeration, and found that the area's consumption demand of natural resources was greater than the natural capital output [11]. Dong used the coupling coordination degree method to evaluate the relations between urbanization degree and ecological environment in the urban agglomeration, and further detected influencing factors of spatial divergence [12]. Peng estimated the future land use of Guanzhong Plain Urban Agglomeration in 2030 using the FLUS model, and simulated the supply and demand of ecosystem services [13].…”
Section: Introductionmentioning
confidence: 99%
“…Yang analyzed the spatio-temporal variations of ecological footprints and ESV from 2005 to 2017 in the Guanzhong Plain Urban Agglomeration, and found that the area's consumption demand of natural resources was greater than the natural capital output [11]. Dong used the coupling coordination degree method to evaluate the relations between urbanization degree and ecological environment in the urban agglomeration, and further detected influencing factors of spatial divergence [12]. Peng estimated the future land use of Guanzhong Plain Urban Agglomeration in 2030 using the FLUS model, and simulated the supply and demand of ecosystem services [13].…”
Section: Introductionmentioning
confidence: 99%
“…This is likely because, with the rapid urbanization of Hubei Province, many people are gathering in cities, urban population density is increasing, and the demand for resources by urban residents have damaged the environment, thus limiting the level of EE. Therefore, it is necessary to strengthen the regional coordination mechanism, clarify the resource endowment advantages and main functions of each city, and vigorously promote the free flow and optimal allocation of production factors within the region ( 75 ). Cities with high coupling coordination, such as Suizhou and Wuhan, should give play to the spatial spillover effect, and promote the synergistic development of surrounding cities; cities with low coupling coordination, such as Xiaogan and Huanggang, should transform their development models and take the needs of economic development and the ecological environment into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…It ensures more realistic results of weight determination. Dong et al (2021) calculated the weights of the indices within the evaluation system via the entropy weight method. The degree of interaction among system indexes is quantified to establish a comprehensive medical evaluation system, so as to promote the medical service system.…”
Section: Entropy Methodsmentioning
confidence: 99%